Rural women’s health: examples of programs designed to support the health aspect of female rural population - Wojcieszak-Zbierska, Monika (Turystyka i Rozwój Regionalny, 2023)
Health is among the important topics addressed at an international level. It largely affects the physical condition of humans, and is a condition for proper physical and mental development. This paper is an overview of programs designed to ensure adequate preventive healthcare and health security for Polish women. It also focuses on presenting selected results of research carried out with a group of female inhabitants of the Gniezno district. The study provides grounds for concluding that while rural women are willing to access the services offered by the National Health Fund, they declare to pay out of their own pocket for half of their specialized doctor appointments.